Prevalence and antibiotic resistance profiles of cerebrospinal fluid bacteria in children- Benghazi (Journal of Medical Sciences, 2020)
Bacterial meningitis is a fatal, restricting endemic disease requiring rapid antibiotic controlling. The objective of this study was to evaluate the antimicrobial sensitivity patterns of microorganisms isolated from CSF to antibiotics. Of 3184 CSF were cultured and sensitivity tests were performed in microbiology department, Pediatric hospital, Benghazi, Libya. The study period was during January 2016 to December 2017. A total 3184 CSF samples, 3149 (99%) CSF samples had no bacterial growth, while 35 (1%) CSF samples showed bacterial growth. 20 (57%) were males and 15 (43%) were females. Staph epidermidis 9 (26%) was more bacteria isolated than patient samples, followed by Gram negative bacteria 7 (21%). Most of the cases were recorded in 28 (80%) winter, followed by 7 (20%) autumn. The bacteria have recorded high sensitivity to chloramphenicol by 23%, followed by Ciprofloxacin 14%, while the highest bacterial resistance was recorded to Septrin by 31%. The early diagnosis and providing treatment early are lifesaving and they reduce chronic morbidity.